2005
DOI: 10.1002/dvdy.20285
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of Wnt signaling-related Dickkopf1, -2, and -3 mRNAs in the developing mouse tooth

Abstract: Wnt signaling is essential for tooth formation. Members of the Dickkopf (Dkk) family modulate the Wnt signaling pathway by binding to the Wnt receptor complex. Comparison of Dkk1, -2, and -3 mRNA expression during mouse tooth formation revealed that all three genes showed distinct spatiotemporally regulated expression patterns. Dkk1 was prominently expressed in the distal, incisor-bearing mesenchyme area of the mandibular process during the initial stages of tooth formation. During molar morphogenesis Dkk1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 39 publications
2
66
1
1
Order By: Relevance
“…In addition, the intensity of Wnt/β-catenin signaling is also regulated by its crosstalk with other signaling pathways. In the developing tooth, several extracellular Wnt antagonists, including Dkks, Sfrps and SOSTDC1, are expressed (Leimeister et al, 1998;Laurikkala et al, 2003;Fjeld et al, 2005), and loss of Smad4 in the dental mesenchyme results in downregulation of the Wnt inhibitors DKK1 and SFRP1, leading to elevated β-catenin activity and subsequent formation of bone-like structure (Li et al, 2011a). In the present study, we show that exogenously applied DKK1 failed to prevent ectopic activation of β-catenin signaling in the incisor mesenchyme and exogenously applied WNT10B could not induce a canonical signaling response in the molar mesenchyme, indicating the…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intensity of Wnt/β-catenin signaling is also regulated by its crosstalk with other signaling pathways. In the developing tooth, several extracellular Wnt antagonists, including Dkks, Sfrps and SOSTDC1, are expressed (Leimeister et al, 1998;Laurikkala et al, 2003;Fjeld et al, 2005), and loss of Smad4 in the dental mesenchyme results in downregulation of the Wnt inhibitors DKK1 and SFRP1, leading to elevated β-catenin activity and subsequent formation of bone-like structure (Li et al, 2011a). In the present study, we show that exogenously applied DKK1 failed to prevent ectopic activation of β-catenin signaling in the incisor mesenchyme and exogenously applied WNT10B could not induce a canonical signaling response in the molar mesenchyme, indicating the…”
Section: Discussionmentioning
confidence: 99%
“…5 Many WNT signaling components are present in developing tooth tissues, with WNT signaling acting at multiple stages, including initiation, morphogenesis, and episodes of hard-tissue formation. [51][52][53][54] Analyses of Sema3A regulation also revealed that WNT4 expressed on early dental epithelium induces not only Sema3A, but also the Msx1 transcription factor. MSX1 is essential for tooth formation in mouse and man, acting within the presumptive dental mesenchyme prior to the arrival of the first dental nerve fibers.…”
Section: Sema3a As a Link Integrating Organogenesis And Innervationmentioning
confidence: 97%
“…Given the paramount role that Wnts play during embryonic development, it is not surprising that one main function of Dkks is to control cell fate in vertebrates as they show highly regionalized expression (Grotewold et al 1999;Monaghan et al 1999;Hashimoto et al 2000;Shinya et al 2000;Chapman et al 2004;Diep et al 2004;Idkowiak et al 2004;Fjeld et al 2005;Nie 2005;Nie et al 2005). Dkk1, -2, and -3 mouse mutants are available and a summary of their phenotypes is presented in Table 1.…”
Section: Role Of Dkks In Embryonic Development and Diseasementioning
confidence: 99%